An Overview of Analytical Methods for the Identification and Quantification of Baclofen - da Silva, Milena N.; da Silva, João Victor Belo; da Fonsêca, Naara Felipe; Oshiro Junior, João Augusto; Dantas Medeiros, Ana Claudia (Current Pharmaceutical Analysis, 2023)
Background: Baclofen is a potent antispasmodic agent, acting as an analgesic and central skeletal muscle relaxant. It is a GABA-B analog, and is widely used for the treatment of spasticity. Due to its therapeutic importance, various analytical techniques are used in the pharmaceutical industry and research to determine, identify, and characterize baclofen in bulk material, biological fluids, and pharmaceutical forms. Objective: This review aimed to collect information on reported analytical techniques commonly used to identify and quantify baclofen in pharmaceutical forms and biological samples. Methods: The authors explored various authenticated scientific journals using these descriptors: highperformance liquid chromatography, liquid chromatography-tandem mass spectrometry, capillary electrophoresis, differential scanning calorimetry, Fourier transform infrared spectroscopy, ultravioletvisible spectroscopy, near-infrared spectroscopy, nuclear magnetic resonance, potentiometry, and Xray diffraction. Results: Quantification of the drug by all the methods evaluated in the review was possible. There were 73 articles reviewed, of which 26 used HPLC for baclofen quantification; the least used was near infrared spectroscopy and potentiometry, both with one article identified. Conclusion: This review has shed light on a wide variety of analytical methods that can be used to quantify and identify baclofen. The knowledge provided by the use of these analytical methods makes this document an important tool for developing pharmaceutical formulations containing baclofen.
Keywords: pharmaceutical formulations